Spiritual Recovery through Dhikr and Faith based on Surah Ar-Ra'd - Irfansya, Rega Ananda; Azizah, Alfiyatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
In the midst of the complex pressures of modern life, many individuals experience mental disorders due to trauma and emotional distress. This research aims to explore the role of dhikr in spiritual recovery, especially based on Surah Ar-Ra'd verses 11, 28, and 29. The method used is a psychological-spiritual approach, which integrates the psychological and spiritual dimensions of Islam. The results of the study show that dhikr can relieve anxiety and increase peace of mind through the release of positive hormones. In conclusion, dhikr is an effective method of overcoming trauma and building emotional stability, and faith and pious deeds are the source of true happiness. This holistic approach offers innovative solutions for mental health recovery in the modern era.